Tribological behavior of ZA27/Al2O3/graphite hybrid nanocomposites. (3rd October 2018) - Güler, Onur; Çuvalcı, Hamdullah; Gökdağ, Mahir; Çanakçi, Aykut; Çelebi, Müslim
ABSTRACT: ZA27 alloy composites reinforced with alumina and graphite nanoparticles are a unique class of advanced engineered materials that have been developed to use in tribological applications. In this study, dry sliding wear behavior of ZA27 alloy matrix hybrid nanocomposites has been investigated. Mechanical alloying and hot pressing methods have been used for the fabrication of these composite materials. Sliding wear tests were conducted using a block-on-disc type sliding wear testing apparatus under unlubricated conditions. Scanning electron microscopy analyses have been carried out to examine the wear surfaces. The results showed that the increase of alumina nanoparticle content can positively influence improvement of the tribological behavior of the hybrid nanocomposites.